2019
DOI: 10.1002/jcp.29287
|View full text |Cite
|
Sign up to set email alerts
|

Role of type 2 innate lymphoid cell and its related cytokines in tumor immunity

Abstract: Type 2 innate lymphoid cells (ILC2s) have multiple functions that can respond to allergic diseases, parasite infection, metabolic homeostasis, tissue repair, and adipose metabolism homeostasis. In these diseases, ILC2s can be activated by various inflammatory cytokines released by damaged cells. Activated ILC2s produce different type 2 cytokines, including interleukin (IL)-4, IL-5, IL-9, and IL-13, which involved in the pathogenesis of many diseases. In recent years, the relationship between ILC2s and tumor di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Recent years, the role of ILC2s in tumor diseases was achieved more and more attention. Studies have proved that ILC2s have a dual role in tumors, so more studies need to be done to detect the real or exactly function in the development of tumor diseases [30,31]. ILC2s are characterized by secreting type 2 cytokines, and the role of ILC2s-derived IL-4, IL-5, IL-9 and IL-13 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years, the role of ILC2s in tumor diseases was achieved more and more attention. Studies have proved that ILC2s have a dual role in tumors, so more studies need to be done to detect the real or exactly function in the development of tumor diseases [30,31]. ILC2s are characterized by secreting type 2 cytokines, and the role of ILC2s-derived IL-4, IL-5, IL-9 and IL-13 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…3.2 Group 1 innate lymphocytes is decreased in colon cancer microenvironment and is positive correlation with M1 phenotype macrophage Previously studies showed that ILCs are abundant in intestinal tissue, and ILC2s-derived IL-4 can promote tumorigenesis by polarizing macrophage towards a pro-tumorigenic M2 phenotype [28][29][30]. Furthermore, group 1 innate lymphocytes are characterized by secreting IFN-γ, which can polarize macrophage towards M1 phenotype [31,32].…”
Section: Macrophage Is Up-regulated In Colon Cancer Microenvironment ...mentioning
confidence: 99%
“…Previously studies have shown that ILCs are abundant in intestinal tissue, and ILC2s-derived IL-4 can promote tumorigenesis by polarizing macrophage towards a pro-tumorigenic M2 phenotype [28][29][30] . Furthermore, group 1 innate lymphocytes are characterized by secreting IFN-γ, which can polarize macrophage towards M1 phenotype 31,32 .…”
Section: Group 1 Innate Lymphocytes Is Decreased In Colon Cancer Microenvironment and Is Positive Correlation With M1 Phenotype Macrophagmentioning
confidence: 99%